Characterisation of a novel gene-targeted model for PRKAG2 disease - Yavari, A (2013)
AMP-activated protein kinase (AMPK) is an evolutionarily highly-conserved serine/threonine kinase that acts as a cellular energy sensor and integrator of metabolic signals at both the cellular and whole-body level. Interest in its cardiac role stemmed from the discovery that dominant mutations in the gene encoding its regulatory γ subunit (PRKAG2) were the cause of a cardiomyopathy characterised by left ventricular hypertrophy (LVH), ventricular pre-excitation, myocardial glycogen storage and progressive cardiac conduction disease. Several cardiac-restricted overexpressing transgenic (TG) murine models have been described which recapitulate much of this, but at the expense of markedly altered γ-isoform stoichiometry and use of an unphysiological promoter, such that overexpressing even wild-type (WT) γ results in glycogen accumulation and LVH. This thesis describes characterisation of the cardiac phenotype and investigation of underlying mechanisms in a novel gene-targeted, knock-in (KI) murine model of PRKAG2 disease carrying an exon 7 R299Q mutation (modelling human R302Q) that was designed to yield new mechanistic insights into the pathophysiology of the cardiomyopathy free of the confounders affecting existing TG models. R299Q mutant transcript expression was verified in the heart, with comparable levels of γ protein expression to WT. Mutant γ2 AMPK complexes demonstrated abrogated allosteric response to AMP and a trend to increased basal activity in vitro. Hearts from mutant mice displayed no visible glycogen excess, but a subtle increase in cardiac glycogen content was apparent in homozygous mutant mice at 12 months of age. On a mixed C57/129 genetic background, mutant mice exhibited mild LV systolic dysfunction at two months of age, but no significant LV remodelling. When backcrossed onto C57BL/6, older mutant mice manifested greater cardiac mass than WT, but in the context of a generalised increased in internal organ and body mass. Homozygous mutant mice displayed intrinsic sinus bradycardia and mild QRS prolongation, but no ventricular pre-excitation. Gene expression profiling and quantitative PCR identified downregulation of Hcn1 and Hcn4 expression in both heterozygous and homozygous mutant mice. These encode f-channels conducting the pacemaker ‘funny’ current (If) and are highly enriched in sinoatrial node (SAN). Isolated SAN myocytes from mutant mice exhibited reduced automaticity and If current density, but no evidence was found for a direct effect of mutant γ2 on f-channels. To investigate whether γ might play a physiological role in the regulation of heart rate, a global γ knock-out (KO) was also generated using Sox2cre to drive embryonic excision of R299Q mutated exon 7 of Prkag2 in the KI. AMPK γ activity was markedly reduced in the hearts of γ KO mice. KO mice had an elevation in intrinsic heart rate and increased Hcn1 and Hcn4 expression. In contrast to γ1, γ transcript was found to be markedly enriched in the atria and SAN of WT mice. These studies indicate that mutant R299Q γ alters SAN automaticity and hence pacemaking via an effect on Hcn expression and If. By inference, the sinus bradycardia and chronotropic incompetence frequently present in carriers of PRKAG2 mutations are likely to reflect a direct effect of mutant γ to induce an f-channelopathy. By providing evidence for effects of mutant γ on cardiac function, electrophysiology (EP) & transcriptome independent of gross glycogen accumulation, the KI model highlights the limitations of conceptualising PRKAG2 disease purely as a glycogen storage disorder and points to the existence of direct, glycogen-independent effects of mutant γ in disease pathogenesis. The directionally opposite EP findings from the γ KO suggest a novel physiological role for γ in the regulation of mammalian heart rate. Investigation of the systemic consequences of gene-targeting Prkag2 with the R299Q mutation revealed a significant metabolic phenotype. Young mutant mice displayed increased lean mass, reduced fat mass, hyperphagia, lower fasting insulin, normal glucose tolerance and increased spontaneous exercise performance. Older mutant mice developed marked obesity – due to hyperphagia rather than reduced energy expenditure – increased somatic growth, impaired glucose tolerance, reduced in vivo glucose-stimulated insulin secretion and lower insulin sensitivity. Prkag2 was seen to be expressed in the arcuate hypothalamus, with increased hypothalamic mRNA expression of the pro-orexigenic agouti-related peptide and the transcription factor BSX – both implicated in the regulation of food intake by the orexigenic hormone ghrelin. Mutant mice displayed an exaggerated food intake response to ghrelin but intact satiety response to leptin, with antagonism of the ghrelin receptor rescuing their hyperphagia. Given the activating nature of these γ mutations and the intense interest in AMPK activation as a therapeutic strategy for the global epidemic of obesity and diabetes, these findings have broad implication in demonstrating the potential risks of chronic AMPK activation in causing hyperphagia and obesity via a ghrelin-dependent mechanism.